Visual Warm-Ups in the Classroom: Student Reflections on Video-Based Learning in Higher Education - Misnawati, Misnawati; Sibali, Alwi; bin Tahir, Saidna Zulfiqar; Ainun Musa, Nur; Ayu Muhammad, Anugrah Puspita (Yayasan Cendekiawan Indonesia Timur, 2025)
This study investigates student perceptions of short video warm-ups used at the beginning of classroom sessions in a higher education English for Professional Purposes (ESP) course. A total of 65 first-semester undergraduate students from seven academic disciplines participated in the study. Using a convergent mixed methods design, both quantitative data from Likert-scale evaluations and qualitative data from open-ended responses were analyzed. Quantitative findings indicated high levels of agreement that the videos increased motivation (M = 4.26), were relevant to the lesson topics (M = 4.26), and aided comprehension (M = 4.23). Thematic analysis of qualitative data revealed six key themes: emotional activation and improved learning atmosphere; cognitive orientation and topic relevance; preferences for engaging media formats; enhanced engagement through real-world connections; technical and language barriers; and suggestions for pedagogical improvement. Students emphasized that short, engaging, and relatable videos helped them transition into learning mode, made the class atmosphere more enjoyable, and supported their understanding of the material. They also expressed a desire for more consistent and interactive integration of video content. The study concludes that short video warm-ups, when well designed and pedagogically aligned, can serve as effective tools for enhancing both cognitive and affective dimensions of learning. The findings offer practical implications for instructors, curriculum designers, and institutions seeking to foster active and student-centered learning environments through digital media.